Precision and Agreement of Individual and Simultaneous Macular and Optic Disc Volumetric Measurements With Spectral Domain Optical Coherence Tomography - Domínguez-Vicent, Alberto; Kensén, Jesper; Ramsay, Marika Wahlberg; Brautaset, Rune; Venkataraman, Abinaya Priya (Frontiers in Medicine, 2021)
Purpose: To evaluate the precision of individual and combined macula and optic disc volumetric analysis, and the agreement between these two scan modes with spectral domain optical coherence tomography (OCT) Methods: Macular and optic disc volumetric measurements were performed with individual and combined scan protocols in one eye of 75 healthy subjects. Three repeated measurements were performed with each protocol. From the macular area, retinal thickness in nine different sectors and ganglion cell complex thickness in eight different sectors were analysed from both scan modes. From the optic disc area, the periparillary retinal nerve fiber layer (pRNFL) thickness in 12 clock sectors and the optic disc parameters were evaluated. For all the parameters, repeatability limit and agreement analysis were performed. Results: For the retinal thickness measurements in macula, the combined scan had 2 to 3 times larger repeatability limit than the individual scan for all the sectors except the central sector, where the repeatability limit was 5 times larger. The limits of agreement intervals were lower than 20 µm for all sectors, except the central. The ganglion cell complex measurements also had larger repeatability limits for the combined scans and the limits of agreement intervals were lower than 10 µm for all sectors. For the pRNFL thickness, the repeatability values were distributed like a vertically elongated ellipse for both scans, but still the repeatability was better for individual scan compared to the combined scan. The shortest and widest interval are obtained for sectors 9 (9 µm) and 12 (40 µm), respectively. The repeatability limit was lower than 0.15 units for all disc parameters with both scan modes. Conclusion: The individual macula and optic disc scans had better repeatability than the combined scan mode, and the two scan modes cannot be used interchangeability due to the wide limits of agreement.